2001
DOI: 10.1074/jbc.m104610200
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylinositol 3-Kinase C2α Contains a Nuclear Localization Sequence and Associates with Nuclear Speckles

Abstract: Phosphoinositide 3-kinase C2␣ (PI3K-C2␣) belongs to the class II phosphatidylinositol 3-kinases, which are defined by their in vitro usage of phosphatidylinositol and phosphatidylinositol 4-phosphate as substrates. All type II phosphatidylinositol 3-kinases contain at their C terminus a C2-like domain. Here we demonstrate that Homo sapiens phosphoinositide 3-kinase C2␣ (HsPI3K-C2␣) has dual cellular localization present in the cytoplasm and in the nucleus. A distinct nuclear localization signal sequence was id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
70
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(75 citation statements)
references
References 52 publications
4
70
1
Order By: Relevance
“…The significance of nuclear PI3 kinases was highlighted by a report that linked nuclear PI3 kinase activity to cyclin D1 expression (51). Other studies have shown that nuclear PI3 kinases localize with subnuclear structures known as nuclear speckles, which contain elements of both transcriptional and pre-mRNA processing machinery (50,52,53). One could speculate that PI3 kinase and its phosphoinositide products may be involved in the arrangement of ordered nuclear structures that facilitate RNA pol II binding to promoters, as shown here, as well as subsequent RNA pol II complex formation, transcriptional elongation, and RNA splicing.…”
Section: Discussionmentioning
confidence: 96%
“…The significance of nuclear PI3 kinases was highlighted by a report that linked nuclear PI3 kinase activity to cyclin D1 expression (51). Other studies have shown that nuclear PI3 kinases localize with subnuclear structures known as nuclear speckles, which contain elements of both transcriptional and pre-mRNA processing machinery (50,52,53). One could speculate that PI3 kinase and its phosphoinositide products may be involved in the arrangement of ordered nuclear structures that facilitate RNA pol II binding to promoters, as shown here, as well as subsequent RNA pol II complex formation, transcriptional elongation, and RNA splicing.…”
Section: Discussionmentioning
confidence: 96%
“…These interchromatin granule clusters contain factors involved in the transcription and processing of pre-mRNA, including RNA polymerase II and splicing factors, and some elements of the PI cycle. PtdIns(4,5)P 2 , PtdIns(4)P 5-kinases (I␣ and II␣), and class II PI3K C2␣ were shown to be associated with nuclear speckles (23,43,44). These results are very intriguing, because class II PI3K is unable to phosphorylate PtdIns(4,5)P 2 whereas active SHIP-2 dephosphorylates PtdIns(3,4,5)P 3 .…”
Section: Discussionmentioning
confidence: 99%
“…However, when fluorescent proteins that bind PtdIns(3)P are expressed in cells, they label endosomes and not the plasma membrane (32,92,318), suggesting that there is little free PtdIns(3)P at the cell surface. There is a recent report that PtdIns3KIIC2␣ localizes to the nucleus rather than the plasma membrane (77). More work is required to determine how PtdIns3KIIC2␣ functions in membrane traffic and to what extent PtdIns(3)P is involved in membrane traffic from the plasma membrane.…”
Section: Ptdins3kiic2␣mentioning
confidence: 99%